The Asphyx - Stephens, Robert, 1931-1995; Powell, Robert, 1944-; Lapotaire, Jane; Scott, Alex, 1929-2015; Arliss, Ralph; Walker, Fiona, 1944-; Comport, Brian; Brittany, John; Newbrook, Peter, 1920- (Hen's Tooth Video, 2009)
A scientist becomes obsessed with the possibility of obtaining immortality by capturing the Asphyx, the essence of death locked deep in our souls.